PAH metabolites in fish bile: From the Seine estuary to Iceland. (March 2017) - Kammann, U.; Akcha, F.; Budzinski, H.; Burgeot, T.; Gubbins, M.J.; Lang, T.; Le Menach, K.; Vethaak, A.D.; Hylland, K.
Abstract: Polycyclic aromatic hydrocarbons (PAH) are environmental contaminants that pose significant risk to health of fish. The International Workshop on Integrated Assessment of Contaminant Impacts on the North Sea (ICON) provided the framework to investigate biomarker responses as well as contaminant concentrations side by side in marine ecosystems. Concentrations of the main PAH metabolites 1-hydroxypyrene, 1-hydroxyphenanthren and 3-hydroxybenzo(a)pyrene were determined in bile by HPLC with fluorescence detection. Fish species under investigation were dab ( Limanda limanda ), flounder ( Platichthys flesus ) and haddock ( Melanogrammus aeglefinus ). A contamination gradient was demonstrated from the low contaminated waters of Iceland and off-shore regions of the North Sea towards higher concentrations in coastal areas. Concentrations of PAH metabolites differed primarily according to sampling region and secondarily to species. Highlights: PAH metabolites are useful for monitoring in marine fish species. A spatial gradient of increasing PAH contamination could be shown. Different fish species could join a pan-European assessment of PAH metabolites. Icelandic fish were used for the calculation of background assessment criteria.